Feasibility of Probabilistic Submarining Prediction in Finite Element Occupant Model Simulations - Renner, Victoria; Sharma, Sumit (My University, 2019)
Current development trends in the automotive industry is heading towards Autonomous Drive (AD) vehicles with novel occupant seating positions, one particular position is reclined seating position. The new seating positions in the car may affect the interaction between the occupant and the seatbelt. In a frontal crash, if the pelvis of an occupant fails to engage properly with the lap-belt, Anterior Superior Iliac Spine (ASIS) slides under the lap-belt and lap-belt loads the abdomen instead of the pelvis bony structures, this is the undesirable event referred to as submarining. To avoid submarining in novel reclined seating position is a key challenge for future AD vehicles. The objective of this thesis was to develop submarining criteria. This master thesis was split into two parts, namely Finite Element (FE) simulations and statistical analysis. The objective of the FE simulations study was to evaluate submarining indicators from the literature and ones developed by thesis student’s engineering judgement. The study simulated two Anthropomorphic Test Devices (Hybrid three 5th and Test Device for Human Occupant Restraint 50th percentile) and one Human Body Model (Total HUman Model for Safety 50th percentile) in three different seating configurations (upright, intermediate reclined and reclined) for three different frontal crash pulses (full frontal rigid barrier and two oblique pulses) using a sled setup to generate submarining and non-submarining data. The full frontal rigid barrier pulse is based on a car’s response in a staged full scale crash test where the car impacts the rigid wall at 56 km/h and the oblique pulses are based on the struck car being impacted by a 2500 kg moving deformable barrier at 90 km/h having a partial overlap from the driver side and passenger side inclined at 15 and -15 along Z-axis respectively. Several submarining indicators were evaluated for the simulated occupant models and the following were found to indicate submarining: ASIS lever arm, ASIS to belt X distance, ASIS X forces and relative angle between lap-belt and pelvis. The results from the FE simulations study were further analysed using statistical analysis using logistic regression. The objective of the statistical analysis was to find an optimal predictor in relation to submarining and to develop a methodology to derive probability curve for submarining which could be further expanded. The most optimal predictor was identified from the smallest value of the Akaike’s Information Criterion and model performance was decided based on the area under the Receiver Operating Characteristics curve. The most optimal predictors were identified as ASIS lever arm and minimum ASIS to belt X distance. The thesis demonstrated that a probabilistic prediction of submarining is feasible, based on analysis of occupant model FE simulation data.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport